Pengaruh Model Pembelajaran dan Asesmen Kinerja terhadap Kemampuan Pemecahan Masalah Matematika - Andri Suryana (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2011)
The objective of this research is to study the effects of learning model and performance assessment model on mathematics problem solving (subject of calculus). An experimental research was conducted at Biology education-UNINDRA.They were selected through multistage random sampling technique. Problem solving test has been employed to collect data which was analyzed by means of two way analysis of variance (ANOVA). Research findings concluded that (1) students who learn under the cooperative learning model show higher then classical learning model in mathematics problem solving (subject of calculus), (2) students receiving Lane Holistic’s performance assessment show higher then Polya’s performance assessment on mathematics problem solving (subject of calculus), (3) there are interaction between learning model, performance assessment model, and mathematics problem solving, (4) in the cooperative learning models group, students receiving Lane Holistic’s performance assessment show lower then Polya’s performance assessment on mathematics problem solving (subject of calculus), (5) in the classical learning models group, students receiving Lane Holistic’s performance assessment show higher then Polya’s performance assessment on mathematics problem solving (subject of calculus), (6) students who are taught mathematics with Lane Holistic’s performance assessment, students who learn under the cooperative learning model show lower then classical learning model in mathematics problem solving (subject of calculus),and (7) students who are taught mathematics with Polya’s performance assessment, students who learn under the cooperative learning model show higher then classical learning model in mathematics problem solving (subject of calculus).